Towards a meaningful engagement approach to mining-induced displacements in South Africa: a legal comparative perspective - Mathiba, Gaopalelwe Lesley (Department of Private Law, 2023)
A few decades ago, it might have been fair to argue that because mining activity is intrinsic to the country's economic growth and development, then everything else negative about mining should just be excused as a 'necessary evil' or 'acceptable collateral damage'. But not now. One of the negative impacts of mining activity is displacement of people. Gaining access to a mineral resource requires displacing local communities to make way for mining operations. This phenomenon is known as mining-induced displacement. In South Africa, Ghana and elsewhere, mining-induced displacements often result in the loss and damage of both tangible and non-tangible assets belonging to the displaced persons. These include homes, livestock, valuable resources, cultural sites, productive lands, social structures, tenure security over traditional lands and livelihoods. With mining-induced displacements, there is also a risk that displaced persons may find themselves homeless, marginalised, jobless and without access to their sustained livelihoods while having lost social cohesion and a sense of belonging. All these have negative bearing not only on the socio-economic realm of those affected, but cultural and moral interests as well. Beyond all these realities, there is not much we know about how and the extent to which meaningful engagement remedy - a dynamic adjudicative strategy devised by the South African courts - may present a solution to the unresolved issues around mining-induced displacements; how the courts have protected the vulnerable against evictions through this remedy; and how such protection could potentially be extrapolated to cover mine-affected communities against displacements in this context. That said, this thesis is an attempt at establishing the potential relationship between meaningful engagement and displacements in mining law. The thesis seeks to answer the overarching research question: How robust and consultative is the regulatory framework in addressing mining-induced displacements in South Africa and Ghana, and to what extent are these frameworks complied with in practice? As far as could be established, there has not been any comprehensive research undertaken to establish the potential nexus between meaningful engagement and displacement within the broader context of mining law in South Africa and Ghana. As such, this thesis advances the proposition that one way of looking at the problem of mining-induced displacement is by considering how the application of meaningful engagement remedy may be extended into mining law to address this unabated problem. The study makes several findings, at a broader level, on how consultative (akin to meaningful engagement) are regulatory frameworks on mining-induced displacements in the two examined jurisdictions. It is found that both jurisdictions have varying degrees of legal protection for the mine-affected communities against displacements. It is also found that there are notable international law norms and standards against displacements that may be instructive to and offer the best frame of reference from which the examined jurisdictions may improve their domestic response to the problem. The stronghold and novelty of this thesis lies in it being the first and by far the most comprehensive analytical research on the potential normative link between meaningful engagement as an adjudicative strategy and mining-induced displacement as a socio-economic and human rights issue from a comparative perspective with a spotlight on Ghana and South Africa; as well as in identifying and analysing more efficient legal mechanisms in international law to deal with the problem.